Nilai-Nilai Religiusitas Adat momeâti pada Masyarakat Kota Gorontalo (Replika Islam Nusantara) - Muhiddin Bakry (Al-Ulum, 2016)
This study aims to make a comprehensive study on the phenomenon of behavior and perception of Gorontalo society to Momeâ€™ati tradition (pledge) as the tradition of Gorontalo society in general, and especially the people of Gorontalo city, which is still maintained, and study of the aspects of religiosity of momeâti custom in society of Gorontalo city. This research is a field research and the data was collected using observation, interviews, Focus Group Discussions (FGD), and documentation. The results of this study reveals that there are some steps in momeâti tradition which doing it. These steps conveys a meaning of religiosity that is in line with the Islamic law. This is one of the local tradition of Gorontalo which has been already assimilated in Islamic values. The implication of this this study can expand and enrich information about local Islamic tradition in Indonesia.